Implementasi Bina Pribadi Islam (BPI) dalam Membina Akhlak Peserta Didik di Sekolah Dasar Inspiratif Al-Ilham Kota Banjar - Fadliyani, Fani; Sahal, Yosep Farhan Dafik; Munawar, Muhamad Aris (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2020)
This study aims: (1) to determine the morals of students in SD Inspiratif Al-Ilham, Banjar City. (2) to determine the implementation of Islamic Personal Development (BPI) in building the morals of students at SD Inspiratif Al-Ilham, Banjar City. (3) to find out the results of the Islamic Personal Development (BPI) in building the morals of students at SD Inspiratif Al-Ilham, Banjar City. The purpose of this study was to determine the morals of students, the implementation of Islamic Personal Development and to find out the results of Islamic Personal Development in fostering the morals of students at SD Inspiratif Al-Ilham, Banjar City. This study used a qualitative research method with a case study approach. This study used data collection techniques using interviews, observation, and documentation study. The data used are primary data obtained directly from respondents regarding the implementation of Islamic Personal Development. Meanwhile, secondary data in the form of theories and other supporting data were obtained from literature and school archives documentation. All of these data are materials to describe the implementation of Islamic Personal Development (BPI) at SD Inspiratif Al-Ilham, Banjar City. The results of this study indicate that: (1) The morals of the students at SD Inspiratif Al-Ilham, Banjar City are good enough. (2) Implementation of Islamic Personal Development in fostering the morals of students at Inspiratif Al-Ilham Elementary School, Banjar City, namely through coaching which includes guidance by exemplary, guidance with habituation and guidance with advice (3) The results of the Islamic Personal Development (BPI) in fostering the morals of students at the Inspiratif Al-Ilham Elementary School, Banjar City are quite good, where students have been able to show behavior according to the existing indicators, including being able to carry out congregational prayers and prayers. sunnah dhuha and qiyamullail, reciting dhikr after every prayer and so on.